Capital Account Liberalization : Does Advanced Economy Experience Provide Lessons for China? - Chelsky, Jeff (World Bank, Washington, DC, 2012)
The initial post World War II pursuit of capital account liberalization (CAL) by advanced economies was Europe-centric, with roots in a broader political rather than economic agenda of greater European integration. In continental Europe, CAL was addressed mostly through the adoption of multilateral instruments and codes. In contrast, CAL by the United States and United Kingdom was pursued unilaterally, motivated by their status as global reserve currency issuers and global financial centers. China's situation is fundamentally different. China today has no equivalent to the European political motivation for CAL or the domestically driven financial motivation of the United States or the United Kingdom. And while China may have long-term aspirations to be a global reserve currency issuer, the extent to which it internationalizes its currency is constrained by powerful domestic economic and political interests that continue to benefit from an export-led growth model underpinned by a pegged and undervalued exchange rate, both of which are difficult to maintain with an open capital account. Alongside China's overarching concern with the maintenance of financial and economic stability, these factors imply a different path for China than paths taken by advanced economies, with significant acceleration in the gradual pace of liberalization unlikely without accelerated development of domestic constituencies that traditionally support CAL.